PERANCANGAN STRATEGI KEUANGAN UNTUK OPTIMALISASI MANAJEMEN KEUANGAN DI AKPER BUNTET PESANTREN CIREBON - Maulana, Yayat (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2025)
This research aims to design a financial strategy that can optimize financial management at AKPER Buntet Pesantren Cirebon. The research focus includes identifying weaknesses in financial planning, management, evaluation, and reporting, as well as developing strategic solutions relevant to the needs of the institution. The method used is a qualitative descriptive approach, with data obtained through interviews, document studies, and direct observation. The results of the study show that financial management at AKPER Buntet Pesantren still faces challenges such as the absence of a performance-based budget, a manual reporting system, and a lack of transparency. To overcome this, the strategy designed includes the implementation of performance-based budgeting, digitalization of the financial system, increased transparency through open reports and regular audits, and diversification of funding sources through grants, donations, and supporting business units. The implementation of this strategy can improve the efficiency of budget allocation, strengthen accountability, and support the sustainability of institutional operations. With these steps, AKPER Buntet Pesantren can optimize its financial management and increase its competitiveness in the world of nursing education.